Nematofauna asociada a la zona urbana de la bahía de Chetumal, Quintana Roo, México - Navarrete, Alberto de Jesús (1999)
Sediments were collected at fifteen stations in five transects at Chetumal Bay (lune and December 1995). Sediments were medium and fine sands with 15.62% organic matter. In lune, 2 239 individuals represented 20 families and 37 genera; in December, 1 426 individuals represented 21 families and 35 genera. Neotonchoides, Desmodora, Bathylaimus, Pseudochromadora, Desrnolaimus, Chromadorina and Steineria were the most abundant. In both months the same transect had the bighest abundance and richness (957 and 744 individuals, 28 and 25 genera, respectively). The lowest abundance in a transect was 48 individuals and six genera. Diversity fluctuated among 0. 53 and 2.53 beleslind. In general, the genus composition in Chetumal bay is homogeneous. The noteworthy occurrence of marine genera in tbis brackish environment shows their adaptability